2011
DOI: 10.1080/19440049.2010.539628
|View full text |Cite
|
Sign up to set email alerts
|

Detection of endogenous steroid abuse in cattle: results from population studies in the UK

Abstract: The use of steroids as growth-promoting agents in food production is banned under European Union legislation. Detecting the abuse of testosterone, nandrolone, boldenone, oestradiol and progesterone is complicated by the fact that these steroids are known to be endogenous in certain situations. In this study, the concentrations of characteristic metabolites of each of these steroids were quantified in populations of untreated steers and heifers. Steroid concentration population data were then used by a statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 13 publications
2
20
0
Order By: Relevance
“…Whether the hormone is exogenous or of natural origin can be determined based on knowledge of marker metabolites, yet only a few of those have been discovered so far (7). Therefore, the majority of methods that have been developed in this field rely on steroid exceeding concentration thresholds as a means of detecting their abuse (17,18). Due to the high variations among concentrations of testosterone in bovine urine under physiological conditions and limited data on its natural level, no acceptable ranges for this hormone are established.…”
Section: Introductionmentioning
confidence: 99%
“…Whether the hormone is exogenous or of natural origin can be determined based on knowledge of marker metabolites, yet only a few of those have been discovered so far (7). Therefore, the majority of methods that have been developed in this field rely on steroid exceeding concentration thresholds as a means of detecting their abuse (17,18). Due to the high variations among concentrations of testosterone in bovine urine under physiological conditions and limited data on its natural level, no acceptable ranges for this hormone are established.…”
Section: Introductionmentioning
confidence: 99%
“…However, as analytical limits of detection decrease, it is also likely that further steroids will be discovered as endogenous in food-producing animals. For example, since the time that the review article of Scarth et al [35] was published, the following steroids have been discovered to be endogenous: 19-noretiocholanolone in boars and gilts, [42] a range of different nandrolone metabolites in steers and heifers, [47,80] wethers, rams and ewes [48] as well as prednisolone in cattle. [81] Furthermore, it has recently been demonstrated that some types of wooden crate in which veal calves are housed may contain precursors to Boldenone.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…-Can be combined with some other screening approaches such as threshold concentrations if the same analytical technique is used. Threshold concentrations (urine, plasma/serum) [42][43][44][46][47][48] -Can be used for both screening and confirmation by using different thresholds.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations